In a dynamic lifting task, the relationship between cross-sectional abdominal muscle thickness and the corresponding muscle activity is affected by the combined use of a weightlifting belt and the Valsalva maneuver - Blanchard, T. W.; Smith, C.; Grenier, S. G. (Journal of Electromyography and Kinesiology, 2016)
It has been shown that under isometric conditions, as the activity of the abdominal muscles increases, the thicknesses of the muscles also increase. The purpose of this experiment was to determine whether change in muscle thickness could be used as a measure of muscle activity during a deadlift as well as determining the effect of a weightlifting belt and/or the Valsalva maneuver on the muscle thicknesses. The Transversus Abdominis (TrA) and Internal Obliques (IO) muscles were analyzed at rest and during a deadlift. Muscle thickness was measured using ultrasound imaging and muscle activity was simultaneously recorded using electromyography. Each subject performed deadlift under normal conditions, while performing the Valsalva maneuver, while wearing a weightlifting belt and while both utilizing the belt and the Valsalva maneuver. There was no relationship between change in muscle thickness and muscle activity for both the TrA and IO (R2 < 0.13 for all conditions). However it was found that the Valsalva maneuver increased abdominal muscle thickness whereas the belt limited muscle expansion; each with an increase in activity. These results indicate that ultrasound cannot be used to measure muscle activity for a deadlift and that the belt affects how the IO and TrA function together.